Analysis of Factors Affecting the Incidence of Chronic Energy Deficiency (SEZ) in Pregnant Women - Taufika Putri Lestari; Sri Mulyaningsih; Yuliandary Yunus; Efri Leny Rauf (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2025)
Chronic Energy Deficiency (KEK) is a condition of long-term malnutrition experienced by pregnant women and has an impact on maternal health and fetal development. In Gorontalo Province, the incidence of SEZ is still quite high, especially in the Limboto Health Center area, there are 199 cases of pregnant women who experience SEZ Incidents. The purpose of this study is to analyze the factors that affect the incidence of Chronic Energy Deficiency (SEZ) in pregnant women at the Limboto Health Center. This study uses a quantitative approach with a cross-sectional design. The sample totaled 288 pregnant women who were selected using purposive sampling techniques. Data was obtained through medical records and analyzed using the Chi-square test. The results showed that the variables of parity (p=0.000), anemia (p=0.000), and ejaculation (p=0.000) had a significant effect on the incidence of Chronic Energy Deficiency (KEK) in pregnant women. Meanwhile, age (p=0.070) and education (p=0.708) did not show a significant effect on the incidence of chronic energy deficiency (SEZ). Parity, anemia, employment, affect SEZ, while age and education have no effect.